Analysis of frozen section compared to permanent section: a 2 year study in a single teritiary care hospital (Journal of Pathology of Nepal, 2021)
Background: Frozen section is a commonly used tool for intraoperative consultation giving valuable information for patient management. Analysis of diagnosis during frozen section and subsequent permanent section allows the pathologist to review the diagnostic accuracy.Materials and methods: In this 2-year retrospective study, 66 tissues received for intraoperative consultation were studied with the corresponding permanent sections on analysis. The diagnosis was either concordant or discordant. The diagnostic accuracy, sensitivity, and specificity were calculated.Results: 65 of 66 cases had a concordant diagnosis on frozen sections and permanent sections. The diagnosis was discordant in one case due to the masking of a tumor by heavy inflammation. The diagnostic accuracy, sensitivity, and specificity were 98.48%, 96.8%, and 100% respectively.Conclusions: The results of our study compared well with those of other institutions, thereby emphasizing the value of frozen sections as a valuable test for intraoperative surgical consultation.